Critical Pedagogy and Language Education: Hearing the Voices of Brazilian Teachers of English - Sávio Siqueira (MDPI AG, 2021)
Based on an ethnographic research study involving Brazilian teachers from different educational contexts in the city of Salvador, Brazil, this paper aims to approach and discuss the dialogic relationship between critical pedagogy and language education, within the context of English as a global lingua franca. The main goal of the original work was to investigate how EFL teachers see themselves as language professionals in the contemporary world, how aware they are of the implications related to the condition of English as an international language or a global lingua franca, and to what extent they conceive teaching the language under a critical intercultural pedagogy. Data were generated through a questionnaire, class observation sessions, and video recordings of semi-structured group interviews in which issues like the globality of English, culture teaching, interculturality, and critical (language) pedagogy were approached and debated. Results have shown that participants are aware of the implications of the global status of English and that teaching the language in these current times cannot happen in a neutral and/or uncritical way. It was also revealed that teachers find difficult to systematize the teaching of culture in their EFL classes, as much as it is challenging for them to see themselves as critical intercultural professionals who can engage in critical pedagogy in their specific educational settings.